Interferensi fonologi pemelajar India dalam pembelajaran BIPA - Saprudin Padlil Syah; Samsi Setiadi; Siti Ansoriyah (Jurnal Bahasa Indonesia bagi Penutur Asing, 2023)
The focus of this research is the interference that occurs when Indian BIPA students learn Indonesian language. The data source for this research is the videos of BIPA Online learning at the Embassy of The Republic of Indonesia in New Delhi and the Consulate General of the Republic of Indonesia in Mumbai facilitated by the National Agency for Language Development and Cultivation. This research is a qualitative study with a case study. The results of this study indicate that phonological interference occurs with the addition of sound, subtraction of sound, and change of sound. First, regarding the addition of sound it can be found that there is interference in the initial sound, namely /i/; and middle sounds, namely /r/, /y/, /g/, /w/, and /h/ sounds. Second, the sound reduction in (1) double vowel /aa/ becomes /a/ and /ii/ becomes /i/; (2) final /ai/ becomes /i/, (3) middle /ŋ/ becomes /n/, (4) middle /ɳ/ becomes /y/, (5) vowel /a/ at the beginning of a word, and (6) the sound /u/ when there are two /us/ sound sandwiching a consonant sound, such as berumur and puluh to be bermur and pluh. Third, sound (1) changes in vowels, that are /ua/ becomes /wa/, /i/ becomes /y/, and /a/ becomes /e/; and (2) changes in consonants, that are /t/ becomes /d/, /v/ becomes /w/, and /w/ becomes /v/.